2019
DOI: 10.12973/ijem.5.4.525
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Resilience and Distress Tolerance in College Students: The Mediator Role of Cognitive Flexibility and Difficulties in Emotion Regulation

Abstract: The purpose of this study is to examine the mediator role of cognitive flexibility and difficulties in emotion regulation in the relationship between resilience and distress tolerance amongst college students. The sample of the study involved 1114 students (771 females, 343 males) from various universities in Turkey. The mean age of the sample was 20.65 (Sd=2.77). The Resilience Scale, Distress Tolerance Scale, Cognitive Flexibility Scale, and Difficulties in Emotion Regulation Scale (DERS) had been used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 42 publications
3
25
2
2
Order By: Relevance
“…Resilience is the capacity of individuals to overcome difficulties and maintain constancy in their lives ( Martin et al, 2015 ; McMurray et al, 2008 ; Waugh et al, 2008 ). Higher levels of resilience and distress tolerance are related to higher levels of cognitive flexibility and emotion regulation ( Arici-Ozan et al, 2019 ); therefore, the “real-world” life experiences of nontraditional students, such as work experience and caring for a family, may help create a more mature and successful student. Resilience will be an important trait in facing the threat of the pandemic.…”
Section: Resilience In Nontraditional Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience is the capacity of individuals to overcome difficulties and maintain constancy in their lives ( Martin et al, 2015 ; McMurray et al, 2008 ; Waugh et al, 2008 ). Higher levels of resilience and distress tolerance are related to higher levels of cognitive flexibility and emotion regulation ( Arici-Ozan et al, 2019 ); therefore, the “real-world” life experiences of nontraditional students, such as work experience and caring for a family, may help create a more mature and successful student. Resilience will be an important trait in facing the threat of the pandemic.…”
Section: Resilience In Nontraditional Studentsmentioning
confidence: 99%
“…The implications of this study suggest that the pandemic will negatively affect all college students’ mental health and well-being, as well as increase the high baseline of sleep disturbances and insomnia already experienced by college students ( Schlarb et al, 2017 ). However, there is good news regarding nontraditional students, in that both age and other nontraditional characteristics are correlated with higher levels of mental health resilience, which is related to the ability to overcome challenges, regulate emotions, and maintain status quo ( Arici-Ozan et al, 2019 ; Martin et al, 2015 ). Therefore, although support services will be needed for all students to ensure their educational goals are attained throughout and after the pandemic, nontraditional students may be better equipped to maintain and return to their previous levels of success.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…This suggests the importance of this EF for tolerance of negative emotions. Regarding the remaining EFs, we found evidence of association—although scarce—between tolerance of negative emotions, and working memory and cognitive flexibility (Arici-Ozcan, 2019; Arici-Ozcan et al, 2019; Macatee et al, 2018). In summary, tolerance of negative emotions showed associations with all EFs, although the results on response inhibition remain contradictory and need to be further explored.…”
Section: Discussionmentioning
confidence: 83%
“…Regarding interference control, two studies found that lower tolerance of negative emotions was associated with greater difficulties in emotional regulation and symptoms of posttraumatic stress among participants with less interference control (Bardeen et al, 2015; Bardeen & Fergus, 2016). About the other two EFs, one study (Macatee et al, 2018) showed a relationship between working memory and tolerance of negative emotions, and two studies (Arici-Ozcan, 2019; Arici-Ozcan et al, 2019) showed a relationship between it and cognitive flexibility. In the first study, working memory was assessed through a behavioral task (Go-NoGo complex with working memory load) and tolerance of negative emotions was assessed through a self-report measure (Distress Intolerance Index).…”
Section: Resultsmentioning
confidence: 99%
“…Behaviour problems within a classroom increase the stress levels of both teachers and students, disrupt the flow of lessons, impede learning objectives and the processes of learning, and negatively affect school climate (Parsonson, 2012). Students with SEBDs also tend to internalise problems such as anxiety and/or withdrawal, which in turn places them at risk of academic failure and dropout (Arici-Ozcan et al, 2019;Gunter et al, 2002;Riney & Bullock, 2012). Challenges in the classroom behavioural management of students with SEBD are usually a great concern for educational professionals; these challenges impact both the student and the classroom as a whole (Chafouleas et al, 2010;Clunies-Ross et al, 2008).…”
Section: Introductionmentioning
confidence: 99%